PENINGKATAN PRODUKTIVITAS KERJA MENGGUNAKKAN METODE 5 S SEKSI PLASTIC INJECTION PT. XYZ - Suwarno, Agus; Salsabila, Shelma Maudy (JURNAL TEKNIK INDUSTRI, 2020)
PT. XYZ is a manufacturing company engaged in the production of automotive components, both two-wheeled and four-wheeled vehicles. A problem was found in the plastic injection work area, there were material remnants and improper placement of work equipment. Background of research in order to increase work productivity in the workplace. This study aims to apply the 5 S method to the conditions in the company. In this study using the 5 S method. The analysis technique used fishbone analysis to determine the cause of the problem of decreasing work productivity. The seiri method is to classify the necessary and unnecessary items. The seiton method is to arrange goods according to the type of goods needed or not needed according to the frequency of use. The seiso method is to remove foreign items so that you get a clean and comfortable work area which is called cleaning. The seiketsu method is to keep things in order and maintain the previous 3 S provisions. The shitsuke method is a habitual activity that makes the 5S as a rule into the company's standard operating system. After applying the 5 S method to work productivity in the work area from September 2019 to October 2019, the average work productivity can be maximized, which has increased significantly, namely 3.6% in September 2019 at 95.3% and in October 2019 by 98.9%.